Adaptive Legal Frameworks and Economic Dynamics in Emerging Tech-nologies: Navigating the Intersection for Responsible Innovation - Lescrauwaet, Lyytinen; Wagner, Hekkert; Yoon, Cheng; Shukla, Sovacool (Law and Economics, 2022)
This research explores the intersection of emerging technologies, including Artificial Intelligence (AI), blockchain, and biotechnology, and the imperative for adaptive legal frameworks to regulate and encourage responsible innovation. Examining historical contexts of technological regulation, the study identifies key lessons from past approaches, emphasizing the need for flexibility, adaptability, and interdisciplinary collaboration. The economic dynamics of emerging technologies reveal both opportunities and challenges, with innovation playing a pivotal role in economic growth. Legal responses and current frameworks are scrutinized, prompting a call for ongoing evaluation and adaptation to the evolving technological landscape. Case studies highlight the effectiveness of existing regulations, while gaps in the regulatory landscape are identified. The concept of an adaptive legal framework emerges as a recommendation, promoting flexibility and agility to address the intricacies of emerging technologies. Balancing stability with adaptability, incentivizing responsible practices, and fostering collaboration among legal, technological, and economic experts are crucial components of effective regulatory measures. The research advocates for building a culture of corporate responsibility, aligning business goals with ethical standards, and promoting education and awareness across all stakeholders. The importance of training for decision-makers, especially policymakers, is underscored as pivotal for informed and ethical governance. In conclusion, this research emphasizes the urgent need for adaptive legal frameworks, interdisciplinary collaboration, continuous education, and a commitment to aligning technological progress with ethical considerations to ensure responsible and ethical innovation in the ever-evolving landscape of emerging technologies.